Tinjauan Yuridis Terhadap Perusahaan Yang Tidak Menjalankan Tanggung Jawab Sosial Perusahaan (CSR) - Cristian Genhart Sirait; Mohammad Reza As Syafi (Universitas Sains dan Teknologi Komputer, 2024)
CSR or corporate social responsibility is an important aspect that was born as a form of corporate responsibility towards social aspects, which includes economic and environmental responsibility. In Indonesia, every company in Indonesia which operates in the field of natural resources is obliged to carry out Social and Environmental Responsibility in accordance with the provisions of Article 74 of Law No. 40 of 2007 which regulates that companies which carry out their business activities in the field and/or related to natural resources are obliged to carry out Responsibility. Social and Environmental Responsibility, Social Responsibility is the Company's obligation which is budgeted and calculated as company costs, the implementation of which is carried out by paying attention to propriety and fairness. Companies that do not carry out social responsibility will be subject to sanctions in accordance with statutory provisions. This research uses normative legal research. This research method is legal research carried out by examining library materials or secondary data. Regulation of obligations for companies in carrying out social responsibility has been regulated in many statutory regulations, however there are still many problems in terms of implementation, due to the lack of clarity regarding the rules regarding sanctions which has led to multiple interpretations. Therefore, new law enforcement is needed, by making the mechanism for implementing sanctions clearer on companies that do not carry out corporate social responsibility.